HIV among Blood Donors in Perak, Malaysia: A Review from 2015 to 2019 - Noor Aqilah Ashamuddin; Sabariah Mohd Noor; Afifa Dzulkafli; Seetha Daywipragas; Thevasree Balakrishnan; Azlina Osman; Ang Ju Ying (Asian Journal of Medicine & Health Sciences, 2022)
Blood donors who are screened positive for HIV will be called for counselling and further management in our tertiary centre in Perak, Malaysia. Nucleic acid testing (NAT) and serological test are used as screening and detection of HIV among blood donors. A cross-sectional study was undertaken from January 2015 to December 2019 by reviewing the existing blood donor database of Hospital Raja Permaisuri Bainun, Ipoh, Perak, Malaysia, that handles more than 314000 blood bags during the study period. 97 individuals were tested positive with HIV, and all of them donated whole blood and the median age was 30 years old. This group of donors comprised different ethnicities (Malay 63.9%, Chinese 15.5%, Indian 18.6% and other ethnicity 2.1%) reflecting the multiracial population of Malaysia. 99% of HIV blood donors were males and more than half of them (63.9%) were single and (57.7%) new donors. 3 donors did not turn up for post-donation counselling, half of them (55.3%) denied practising any high-risk behaviours, while 44.7% of them revealed their past involvement in one or two high-risk behaviours. The most commonly reported high-risk behaviour was practising the lifestyle of casual sex or multiple sexual partners (19.1%), followed by men having sex with men (MSM) (15.1%) and "make or received payment in exchange for sex" (11.7%). It is pivotal to maintain the equilibrium between recruiting blood donors and at the same time educating those with high-risk behaviours to defer themselves prior to donating. HIV infection among blood donors remains a threat to Blood Transfusion Services (BTS) in Malaysia.